Diagnosis and management of Duchenne muscular dystrophy, part 1: diagnosis, and neuromuscular, rehabilitation, endocrine, and gastrointestinal and nutritional management. Issue 3 (March 2018) - Birnkrant, David J; Bushby, Katharine; Bann, Carla M; Apkon, Susan D; Blackwell, Angela; Brumbaugh, David; Case, Laura E; Clemens, Paula R; Hadjiyannakis, Stasia; Pandya, Shree; Street, Natalie; Tomezsko, Jean; et al.
Summary: Since the publication of the Duchenne muscular dystrophy (DMD) care considerations in 2010, multidisciplinary care of this severe, progressive neuromuscular disease has evolved. In conjunction with improved patient survival, a shift to more anticipatory diagnostic and therapeutic strategies has occurred, with a renewed focus on patient quality of life. In 2014, a steering committee of experts from a wide range of disciplines was established to update the 2010 DMD care considerations, with the goal of improving patient care. The new care considerations aim to address the needs of patients with prolonged survival, to provide guidance on advances in assessments and interventions, and to consider the implications of emerging genetic and molecular therapies for DMD. The committee identified 11 topics to be included in the update, eight of which were addressed in the original care considerations. The three new topics are primary care and emergency management, endocrine management, and transitions of care across the lifespan. In part 1 of this three-part update, we present care considerations for diagnosis of DMD and neuromuscular, rehabilitation, endocrine (growth, puberty, and adrenal insufficiency), and gastrointestinal (including nutrition and dysphagia) management.